Hydrochemical and Hydroacoustic Investigation of the Yugama Acid Crater Lake, Kusatsu-Shirane, Japan - Hernández, Pedro A.; Nogami, Kenji; Padrón, Eleazar; Somoza, Luis; Amonte, Cecilia; Mori, Toshiya; Melián, Gladys V.; Sumino, Hirochicka; Kikawada, Yoshikazu; Pérez, Nemesio M. (Frontiers in Earth Science, 2021)
We report the results of an interdisciplinary study carried out in August 2013 consisting of the first estimation of rate of diffuse CO2 emission, the chemical and isotopic analysis of water and dissolved gases in samples from vertical lake profiles, and an echo-sounding survey of the crater lake Yugama, Kusatsu-Shirane volcano.. The lake water has an average temperature of 24-25ºC, pH 1.01, SO42- between 1,227-1,654 mgL-1 and Cl- 1,506-2,562 mgL-1, with gas bubbling at several locations and floating sulfur globules with sulfide inclusions. A total of 66 CO2 efflux measurements were taken at the lake surface by means of the floating accumulation chamber method to estimate the diffuse CO2 output from the studied area. CO2 efflux values ranged from 82 up to 25,800 g m−2 d−1. Estimation of the diffuse CO2 emission at Yaguma Crater Lake was 30 ± 12 t d−1. Normalized CO2 emission rate (assuming an area of 0.066 km2) was 454 t km−2 d−1, a value within the range of acid volcanic lakes. Vertical profiles of major ions and dissolved gases showed variations with increases in ion content and dissolved CO2 and He with depth. Acoustic imaging shows the presence of intense bubbling and provides important information on the bathymetry of the lake. The 50–200 kHz echograms exhibit frequent vertical plumes of rising gas bubbles. Within the crater-lake, three circular submarine vents have been identified showing flares due to a significant activity of sublacustrine emissions. Periodic hydrogeochemical and hydroacoustic surveys at Yugama Crater Lake, whenever the level of volcanic activity allows it, may thus help to document changes in the state of activity of this high-risk volcanic area, and lead to the development of better precursor parameters for magmatic volcanic activity.